Molecular Variants of Human Papillomavirus among Individuals Attending Healthcare Checkup in Everight Diagnostic and Laboratory Services Owerri, Imo State, Nigeria - O. Ekuma-Okereke; A. S. Aleke; C. O. Anyanwu; J. A. Ugwu; A. E. Emedoh; C. G. Omejua; V. C. Onuoha; U. O. Nwankpa; C. P. Nduwuaku; C. C. Adiele; B. C. Iwuala; I. Onyema-Nwankwo (Archives of Current Research International, 2023)
Background: Human papillomaviruses (HPV) are small, non-enveloped, epitheliotropic, double-stranded DNA viruses that infect mucosal and cutaneous epithelia in a wide variety of higher vertebrates in a species-specific manner and induce cellular proliferation. Papilloma viruses are highly epitheliotropic, with a highly host-specific affinity and humans are the only host of HPV. HPV Array Test can detect up to 33 genotypes; which according to the research result of the WHO International Agency for Research on Cancer (IARC), are classified as Low Risk types (6, 11, 42, 43, 44 & 81) which can cause the skin mucosa wart-like lesions; HPV 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59 & 68 are classified as high-risk types; HPV 26, 53, 66, 73 & 82 genotypes are classified as middle-risk types. Aim: This study was designed to determine and classify the molecular variants of HPV among individuals attending healthcare checkup in the Molecular Science and Genetic Studies Department of Everight Diagnostics, Owerri. Methodology: HPV Array test relies on PCR amplification and “Flow-through” hybridization technology. Genomic DNA of the human papilloma viral isolates from tissue samples were extracted using MN Research Bacterial DNA MiniPrepTM Kit. A pool of results was collated from 163 individuals whose urethra and endo-cervical swab samples had been collected and processed accordingly. Results: The demographic distribution of the study population show 66.25% and 33.74% for female and male respectively while the mean age was 38.34±13.63. Out of the 163 individuals recruited, 50 (30.66%) were HPV positive with the highest prevalence of 22.08 % in females while males recorded 8.58%. High-risk HPV had the highest prevalence of 34 (68%), while 8 (16%) and 8 (16%) were recorded for low and medium risks respectively. The most common genotypes were HPV 16 (8%), HPV 35 (8%), HPV 39 (8%), and HPV 51 (8%). High-risk dual infection was recorded in 7 (13%) while 5 (10%) had multiple high-risk HPV infections. HPV 11 (6%) was the highest occurring low-risk HPV infection while HPV 6 and 11 3(6%) were the most occurring dual low-risk HPV genotypes. No cases of multiple low-risk HPV infections were recorded in this study. Conclusion: The research findings show HPV-16, 35, 39 and 51 as the predominant genotypes amongst the screened individuals. These are high-risk-human papilloma viral genotypes that predispose individuals to cervical and/or urethral cancers, with HPV-16 standing at the top of the hierarchy, followed by HPV-33 and HPV-31.